1991
DOI: 10.1111/j.1476-5381.1991.tb12279.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperosmolarity on human isolated central airways

Abstract: We studied the effect of hyperosmolarity on human isolated airways because a better understanding of the effect of hyperosmolarity on the human airway wall may improve insight into the pathophysiology of hyperosmolarity‐induced bronchoconstriction in asthma. In cartilaginous bronchial rings dissected from fresh human lung tissue, hyperosmolar Krebs‐Henseleit buffer (450 mosm, extra sodium chloride added) evoked a biphasic response: a rapid relaxation phase (peak after 5.0 ± 0.3 min) followed by a slow contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…substance P) [19] from sensory nerves, which have been shown to increase ciliary beat frequency [20][21][22]. Histamine has been demonstrated to increase MCC both in asthmatic and healthy subjects [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…substance P) [19] from sensory nerves, which have been shown to increase ciliary beat frequency [20][21][22]. Histamine has been demonstrated to increase MCC both in asthmatic and healthy subjects [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…substance P) from sensory nerves [18]. Animal studies, in vitro and in vivo, have shown that chemical mediators and neuropeptides can stimulate ciliary activity [19][20][21] by a mechanism which is not clearly understood but may involve neural stimulation of ciliary beat frequency via the cyclooxygenase pathway [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MCC is most likely to be due to mediators released in response to hyperosmolarity of the airway surface liquid, because exposure of the human airways to a hyperosmolar stimulus causes release of histamine, prostaglandin E 2 (PGE 2 ) and leukotriene C 4 from the mast cells [15][16][17][18], and possibly neuropeptides (e.g. substance P) from sensory nerves [18].…”
Section: Discussionmentioning
confidence: 99%
“…histamine), and sensory nerves (e.g. substance P) [32], as these mediators are known to stimulate ciliary activity and mucus transport mechanisms [33][34][35]. It is possible that inhibition or blocking of mediator release from mast cells [11], and neuropeptides from sensory nerves [36], by frusemide could cause a transient delay in the increase in MCC after ISH with dry air in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%